2008
DOI: 10.1186/1471-213x-8-41
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of microRNAs from rainbow trout (Oncorhynchus mykiss): Their expression during early embryonic development

Abstract: Background: Current literature and our previous results on expression patterns of oocytespecific genes and transcription factors suggest a global but highly regulated maternal mRNA degradation at the time of embryonic genome activation (EGA). MicroRNAs (miRNAs) are small, non-coding regulatory RNAs (19-23 nucleotides) that regulate gene expression by guiding target mRNA cleavage or translational inhibition. These regulatory RNAs are potentially involved in the degradation of maternally inherited mRNAs during e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 36 publications
8
62
0
Order By: Relevance
“…MiRNAs can be identified by direct cloning (Ramachandra et al, 2008;Sunkar et al, 2005), high-throughput sequencing (Chi et al, 2011;Soares et al, 2009) and computational homology-based methods (Jones-Rhoades and Bartel, 2004;Li et al, 2010). And recently, a lot of miRNAs have been identified by high-throughput sequencing in various animals and plants for its high performance, including rainbow trout (Ma et al, 2012).…”
Section: Identifying Potential Mirnas In Rainbow Troutmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs can be identified by direct cloning (Ramachandra et al, 2008;Sunkar et al, 2005), high-throughput sequencing (Chi et al, 2011;Soares et al, 2009) and computational homology-based methods (Jones-Rhoades and Bartel, 2004;Li et al, 2010). And recently, a lot of miRNAs have been identified by high-throughput sequencing in various animals and plants for its high performance, including rainbow trout (Ma et al, 2012).…”
Section: Identifying Potential Mirnas In Rainbow Troutmentioning
confidence: 99%
“…And large numbers of miRNAs have been successfully identified through comparative genomic computational strategies in a wide range of animals and plants (Bonnet et al, 2004;Lim et al, 2003). However, as for rainbow trout, regarded as the "aquatic lab-rat" and the most-widely cultivated cold freshwater fish species in the world (Palti et al, 2011), only limited researches have been performed experimentally (Ma et al, 2012;Ramachandra et al, 2008;Salem et al, 2010) and no studies about miRNAs have been reported via the computational approaches considering the large numbers of EST (expression sequence tags) available in the public database.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al 22 have shown that miR-21 could be detected from early developmental stages (12 h) and constituted up to 40% of all miRNAs in fibroblasts, irrespective of tissue of origin in developing zebrafish embryo. In another study involving rainbow trout (Oncorhynchus mykiss), 23 it was shown that expression levels of miR-21 and Stat3, which is one of the transcription factors regulating miR-21, 9 miRNA expression analysis of monocytes from children with allergic rhinitis has indicated that miR-21 is one of the miRNAs that were most significantly downregulated in allergic rhinitis and this decrease in miR-21 expression is coupled with enhanced miR-21-target gene TGFb receptor 2 (TGFBR2). 71 However, it is not known whether targeting of TGFBR2 by miR-21 has any functional consequence in allergic rhinitis.…”
Section: Role Of Mir-21 In Developmentmentioning
confidence: 99%
“…Although hundreds of miRNAs have been identified, only very small number of lower vertebrates (such as teleost) miRNAs have been discovered and functionally identified. People have been used a classic method to cloned and identified miRNAs directly from zebrafish and rainbow trout [12,13]. However, because of all miRNAs have similar secondary hairpin structures and many of these structures are evolutionarily conserved, it is difficult to clone it from low-abundance miRNAs [14].…”
mentioning
confidence: 99%